Clinical significance of CT angiographic assessment of collateral circulation combined with serum NLRP1 levels in ischemic stroke patients - Tao, Chong; Wang, Yu; Xiao, Shiyin (Medicine (Baltimore), 2023)
This research aimed to combine serum NLR-pyrin domain containing 1 (NLRP1) levels and collateral circulation to assess ischemic stroke patients and predict the prognoses of the patients. This present prospective observational study enrolled 196 ischemic stroke patients. All patients underwent CTA as well as digital subtraction angiography (DSA) to assess collateral circulation by American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR). In addition, we collected serum samples from 100 patients with carotid atherosclerosis as controls. The serum NLRP1, tumor necrosis factor α (TNF-α), interleukin (IL)-6, IL-1β and C-reactive protein (CRP) levels were measured by enzyme-linked immunosorbent assay (ELISA). The age, BMI, sex, smoke condition, diastolic blood pressure, systolic blood pressure, National Institutes of Health Stroke Scores (NIHSS), modified Rankin Scale (mRS) scores, imaging indicators and the levels of triglyceride, total cholesterol (TC), low-density leptin cholesterol (LDLC), high-density leptin cholesterol of all subjects were recorded. All data used SPSS 18.0 to statistical analyses. The serum levels of NLRP1 were remarkably enhanced in the ischemic stroke patients compared with the carotid atherosclerosis patients. The NIHSS score, the mRS score after 90 days and the levels of NLRP1, CRP, TNF-α IL-6 and IL-1β of ischemic stroke patients in the ASITN/SIR grade 0 to 2 group were remarkably elevated than the ischemic stroke patients in ASITN/SIR grade 3 to 4 group. Spearman analysis supported that a positive correlation existed among the NLRP1, CRP, IL-6, TNF-α, and IL-1β levels. The NIHSS score, infarct volume and the levels of NLRP1, IL-6, TNF-α, and IL-1β of ischemic stroke patients in the mRS score ≥ 3 group were remarkably elevated than the ischemic stroke patients in the mRS score ≤ 2 group. ASITN/SIR grade and NLRP1 could be potential diagnostic biomarkers of poor prognosis of ischemic stroke patients. It was found that NLRP1, ASITN/SIR grade, infarct volume, NIHSS, IL-6, and IL-1β were the risk factors for bad prognosis of ischemic stroke patients. This study showed that the serum NLRP1 levels were remarkably decreased in ischemic stroke patients. In addition, the serum NLRP1 levels and ASITN/SIR grade could predict the prognosis of ischemic stroke patients.